Upaya Peningkatan Mutu Pelayanan Melalui Pelatihan Keperawatan Islami Berbasis Standar Akreditasi RS Islam (MUKISI). - Hasanah, Idyatul; Hadi, Irwan; Idris, Baiq Nurainun Apriani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Islamic health training is an effort to achieve health quality based on sharia hospital accreditation standards. RSI Siti Hajar Mataram as a location of service has an important role in providing services based on Islamic values. This service aims to be able to improve the quality of health services through Islamic health training based on sharia hospital accreditation standards. Activities are carried out with socialization, training, mentoring, application of technology and evaluation. The result of this service is an increase in knowledge and attitudes and Islamic Health Training Based on Islamic Hospital Accreditation Standards (MUKISI) at RSI Siti Hajar Mataram has been successfully held involving 70 participants from various health worker professions. This training is designed to improve the understanding and skills of medical personnel in providing services based on Islamic values according to Islamic hospital accreditation standards